Increasing the Competeny of Tourist Destination Management Employees - Milang, Ichsan (Yayasan Pendidikan Belajar Berdikari, 2024)
This study is based on employee competency for managing tourism item destinations at GarutRegency's tourism and culture department. The author is exploring this issue because he wants to learn more about staff competency for managing tourist item destinations in the District tourist and Culture Department's Destination Sector, Pangandaran. Several issues have been identified based on field observations, including knowledge, understanding, ability/skills, values, attitudes, and interests. The aims of this study are 1) to determine staff competence for managing tourism destinations in the tourism and culture department of GarutRegency. 2) To identify the dimensions that were examined in terms of staff competency for managing tourism destinations in GarutRegency's tourism and cultural departments. With this research, the author used a qualitative approach and descriptive method, data collection techniques using interviews, which were carried out with the head of the Head of General and Civil Service Sub-department, the Head of Sub-Destination UPT GarutRegion and the Sub-General and Personnel Apparatus of the tourism and culture office of Pangadaran Regency, observations and documentation.